2012
DOI: 10.1149/2.062212jes
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Glucose/O2Biofuel Cell: Effect of Utilizing Purified Laccase with Anthracene-Modified Multi-Walled Carbon Nanotubes

Abstract: Laccase, a blue multicopper oxidoreductase enzyme, is a robust enzyme that catalyzes the reduction of oxygen to water and has been shown previously to perform improved direct electron transfer in a biocathode when mixed with anthracene-modified multi-walled carbon nanotubes. Previous cathode construction used crude laccase enzyme isolated as a brown cell extract powder containing both active and inactive proteins. Purification of this enzyme, yielding a blue solution, resulted in greatly improved enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…The first category can be further separated into two subcategories composed by enzymes [13], [14] and bacteria [12], [15] respectively. It was shown that the utilization of enzymes for the ORR such as bilirubin oxidase [16], [17], [18], [19], laccase [20], [21], [22] and ascorbate oxidase [22], [23], [24] enhances dramatically the reaction with low overpotentials (within 100 mV) and high reaction kinetics [25], [26], [27]. Unfortunately, due to the low number of active sites, limiting current occurs at relatively low current densities [19].…”
Section: Introductionmentioning
confidence: 99%
“…The first category can be further separated into two subcategories composed by enzymes [13], [14] and bacteria [12], [15] respectively. It was shown that the utilization of enzymes for the ORR such as bilirubin oxidase [16], [17], [18], [19], laccase [20], [21], [22] and ascorbate oxidase [22], [23], [24] enhances dramatically the reaction with low overpotentials (within 100 mV) and high reaction kinetics [25], [26], [27]. Unfortunately, due to the low number of active sites, limiting current occurs at relatively low current densities [19].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In addition the strategy of wiring enzymes has been utilized in developing electrochemical immunoassays, [12][13][14] DNA detection, 15 and enzymatic biofuel cells. [16][17][18][19] Another advantage of redox polymers is that they have demonstrated an ability to electrically communicate with a wide range of redox enzymes such as: amine oxidase, 4 bilirubin oxidase, 20 glucose oxidase, 21 glucose dehydrogenase, 22 lactate oxidase, 9 glycerol oxidase, 9 laccase, 23,24 pyruvate oxidase, 8 horseradish peroxidase, 25 and sulfite oxidase. 3 Given the widespread use of redox polymers it is surprising that there are only a handful reports of combining the enzyme fructose dehydrogenase (FDH) with redox polymers (Table I).…”
mentioning
confidence: 99%
“…Using controlled immobilization strategies, the onset potential for DET may be shifted higher, 39,40,53 but DET is not observed under the present, less controlled conditions. This may be further explained by the relatively small fraction of laccase that resides within electron Table III tunneling distance of the gold surface.…”
Section: Resultsmentioning
confidence: 61%